2012
DOI: 10.1007/s10681-012-0777-y
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme activity in wheat breeding lines derived from matings of low polyphenol oxidase parents

Abstract: Polyphenol oxidase (PPO) in grain plays a major role in time-dependent discoloration of wheat (Triticum aestivum L.) products, especially fresh noodles. Breeding wheat cultivars with low or nil PPO activity can reduce undesirable product darkening. The low PPO line PI 117635 was crossed to two low PPO wheats, IDO580 and 'IDO377s', to determine whether matings between wheats with low levels of grain PPO would result in complementation, such that lines with still lower or nil PPO would be generated. Progeny in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…demonstrated that in five different wheat populations, Ppo‐A1 and Ppo‐D1 alleles, as identified by molecular markers, were highly related to levels of kernel PPO activity. Nilthong et al . went on to show that crossing and selection could generate hexaploid wheat lines with PPO levels (by L‐DOPA) not different from the durum cultivar ‘Ben.’ Hystad et al .…”
Section: The Role Of Polyphenol Oxidase (Ppo)mentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that in five different wheat populations, Ppo‐A1 and Ppo‐D1 alleles, as identified by molecular markers, were highly related to levels of kernel PPO activity. Nilthong et al . went on to show that crossing and selection could generate hexaploid wheat lines with PPO levels (by L‐DOPA) not different from the durum cultivar ‘Ben.’ Hystad et al .…”
Section: The Role Of Polyphenol Oxidase (Ppo)mentioning
confidence: 99%
“…Nilthong et al 129 demonstrated that in five different wheat populations, Ppo-A1 and Ppo-D1 alleles, as identified by molecular markers, were highly related to levels of kernel PPO activity. Nilthong et al 130 went on to show that crossing and selection could generate hexaploid wheat lines with PPO levels (by L-DOPA) not different from the durum cultivar 'Ben.' Hystad et al 75 showed that combining 'null' PPO alleles at PPO-A1 and PPO-D1 resulted in lower PPO activity, and brighter white salted noodles with lower discoloration (ΔL*).…”
Section: Genetic Differences In Ppomentioning
confidence: 99%
“…Ppo-A2d contains a single aspartate to glycine mutation in the second exon at position 400 of the 577 residue polypeptide. Note that the use of complimentary STS markers PPO16/STS01 and PPO29 which discriminate between Ppo-D1 alleles associated with high (Ppo-D1b) and low (Ppo-D1a) PPO activity will give conflicting results in the 07OR1074 genetic background (Onto 2011;Nilthong et al 2012Nilthong et al , 2013. As the Ppo-D1f allele is identical in structure and nearly identical in sequence to the Ppo-D1b allele with the exception of a single SNP, PPO29 is unable to distinguish the high-PPO allele (Ppo-D1b) and null allele (Ppo-D1f) explaining erroneous results obtained in prior reports.…”
Section: Discussionmentioning
confidence: 99%
“…The major genes governing kernel PPO activity have been reported to be present in wheat homeologous group 2 chromosomes (Jime´nez and Dubcovsky, 1999). The role of the PPO genes on chromosome 2AL and 2DL (i.e., PPOA1 and PPOD1) in regulating kernel PPO activity has been established (Sun et al, 2005;Chang et al, 2007;He et al, 2007;Wang et al, 2009) and the PPOA1 locus has been found to have major effect in determining kernel PPO activity (Raman et al, 2007;Beecher and Skinner, 2011;Martin et al, 2011;Nilthong et al, 2013). In order to facilitate marker assisted selection (MAS), reproducible gene-based sequence tag site (STS) markers have been developed for the PPOA1 and PPOD1 loci.…”
Section: Introductionmentioning
confidence: 99%
“…In order to facilitate marker assisted selection (MAS), reproducible gene-based sequence tag site (STS) markers have been developed for the PPOA1 and PPOD1 loci. However, the possibility of erroneous prediction of alleles at PPOD1 locus using the developed markers has been indicated (Nilthong et al, 2013). In the recent past, 4 QTLs for PPO activity on chromosomes 2AL, 3BS, 4BL and 7DL has been documented to explain 64.1-89.0 % of the total phenotypic variance across environments (Zhai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%